2003
DOI: 10.1046/j.1439-0531.2003.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genome in Embryo Technologies

Abstract: The mammalian mitochondrial genome encodes for 37 genes which are involved in a broad range of cellular functions. The mitochondrial DNA (mtDNA) molecule is commonly assumed to be inherited through oocyte cytoplasm in a clonal manner, and apparently species-specific mechanisms have evolved to eliminate the contribution of sperm mitochondria after natural fertilization. However, recent evidence for paternal mtDNA inheritance in embryos and offspring questions the general validity of this model, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 139 publications
(310 reference statements)
0
10
0
Order By: Relevance
“…It has been speculated that induced artificial heteroplasmy could be responsible for low SCNT efficiency [37], but two fetuses in resorption that yielded DNA and could be assayed for heteroplasmy in our study turned out to be homoplasmic for oocyte mtDNA. Mitochondrial functions are nevertheless extremely diverse and complex [38], and natural variation in the mitochondrial genome affects a variety of parameters in natural and assisted reproduction [39]. Smith et al [40] reported mtDNA effects on blastocyst rate in reconstructed mouse embryos; epigenetic effects seemed negligible in this model.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been speculated that induced artificial heteroplasmy could be responsible for low SCNT efficiency [37], but two fetuses in resorption that yielded DNA and could be assayed for heteroplasmy in our study turned out to be homoplasmic for oocyte mtDNA. Mitochondrial functions are nevertheless extremely diverse and complex [38], and natural variation in the mitochondrial genome affects a variety of parameters in natural and assisted reproduction [39]. Smith et al [40] reported mtDNA effects on blastocyst rate in reconstructed mouse embryos; epigenetic effects seemed negligible in this model.…”
Section: Discussionmentioning
confidence: 90%
“…The observed differences are relevant for and could improve SCNT cloning efficiency and, if present in human, might have consequences for technologies such as ooplasmic transfer in assisted reproduction [39,45]. Our data point to complex oocyte cytoplasm-dependent epigenetic modifications and/or nuclear DNA-mtDNA interactions that could be functionally dissected by SCNT after controlling the nuclear genome of oocyte donors by repeated backcrossings [38], or by using groups of transmitochondrial individuals [46] as oocyte donors for the production of embryos, fetuses, and offspring in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…A non-coding mitochondrial control region contains the main regulatory sequences for transcription and replication initiation, including a triplestranded D-loop. Though the great majority of mitochondrial proteins are encoded by the nuclear genome, mtDNA encodes 13 proteins involved in oxidative phosphorylation (for review see Hiendleder &Wolf, 2003 andFernandez-Silva et al, 2003). Individual mammalian mitochondrial-genome-encoded genes have demonstrated a number of other important biological functions, such as serving as histocompatibility antigens for the NADH dehydrogenase 1 (mt-Nd1) and cytochrome c oxidase subunit I (mt-Co1)-derived peptides (Loveland et al, 1990 ;Morse et al, 1996) or playing a role in protein folding for 12S and 16S ribosomal RNA (mt-Rnr1 and -Rnr2 ; Sulijoadikusumo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In SCNT embryos, nuclear-mitochondrial interaction is complicated by the fact that the donor nucleus has to function properly in either a heteroplasmic environment consisting of two mitochondrial lineages or a homoplasmic environment consisting of a mitochondrial lineage unrelated to the nuclear genome. Heteroplasmy has been associated with poor developmental outcome in SCNT embryos and possibly with the phenotypic variation observed in cloned offspring [14]. Examination of heteroplasmic SCNT embryos produced from Bos taurus oocytes and donor cells of different mtDNA haplotypes indicates that the type of recipient cytoplasm affected the developmental ability of the embryo and the fetus, with changes in fetal phenotype and fetal cell metabolism being observed [15].…”
Section: Introductionmentioning
confidence: 99%